The heart's rhythm ‘n’ blues: sex differences in circadian variation patterns of vagal activity vary by depressive symptoms in predominantly healthy employees - Jarczok, Marc N.; Aguilar-Raab, Corina; Koenig, Julian; Kaess, Michael; Borniger, Jeremy C.; Nelson, Randy Joe; Hall, Martica; Ditzen, Beate; Thayer, Julian F.; Fischer, Joachim E. (Chronobiology international, 2018)
Introduction: Successful regulation of emotional states is positively associated to mental health, while difficulties in regulating emotions are negatively associated to overall mental health and in particular associated with anxiety or depression symptoms. A key structure associated to socio-emotional regulatory processes is the central autonomic network. Activity in this structure is associated to vagal activity can be indexed noninvasively and simply by measures of peripheral cardiac autonomic modulations such as heart rate variability. Vagal activity exhibits a circadian variation pattern, with a maximum during nighttime.Depression is known to affect chronobiology. Also, depressive symptoms are known to be associated with decreased resting state vagal activity, but studies investigating the association between circadian variation pattern of vagal activity and depressive symptoms are scarce. We aim to examine these patterns in association to symptom severity of depression using chronobiologic methods.Methods: Data from the Manheim Industrial Cohort Studies (MICS) were used. A total of 3,030 predominantly healthy working adults underwent, among others, ambulatory 24-h hear rate-recordings, detailed health examination and online questionnaires and were available for this analysis. The root mean sum of successive differences (RMSSD) was used as an indicator of vagally mediated heart rate variability. Three individual-level cosine function parameters (MESOR, amplitude, acrophase) were estimated to quantify circadian variation pattern. Multivariate linear regression models including important covariates such as age, sex, and lifestyle factors as well as an interaction effect of sex with depressive symptoms were used to estimate the association of circadian variation pattern of vagal activity with depressive symptoms simultaneously.Results: The analysis sample consisted of 20.2% females and an average age 41 with standard deviation of 11 years. Nonparametric bivariate analysis revealed significant MESOR and amplitude differences between the 90th percentile split, but not on acrophase.Multivariate linear regression models estimated depressive symptoms to be negatively associated with the 24h mean (MESOR) and oscillation amplitude in men but positively associated in women. This pattern of findings indicates a blunted day-night rhythm of vagal activity in men with greater depressive symptoms as well as a moderation effect of sex in the association of CVP and depressive symptoms.Conclusions: This is the first study investigating circadian variation pattern by mild depressive symptoms in a large, rather healthy occupational sample. Depressive symptoms were associated with decreased circadian variation pattern of vagal activity in men but with increased circadian variation pattern in women. The possible underlying mechanism(s) are discussed using the neurovisceral integration model. These findings may have implications for the knowledge on etiology, diagnosis, course, and treatment of depressive symptoms and thus may be of significant public health relevance.